Development of human resources in implementing aircraft maintenance - Fu'ad, Izzulhaq Khoirul; Gunawan, Gunawan; Edi, Prasetyo (Vortex, 2024)
HR is the main factor that determines the life or death of an organization, both business and social organizations, HR planning is a science that has a specific object of study and is made a compulsory subject, both at the diploma, undergraduate, and postgraduate levels. activities carried out on an ongoing basis to improve employee competence and organizational performance through training, education, and career development programs. Human resource competency standards are the first door that must be passed by human resources who will be involved in the world of aviation to evaluate and analyze human resources development in the field of aircraft maintenance. The method in this study uses a qualitative approach using SWOT analysis which identifies opportunities and threats that exist in the macro environment and industry as well as the company's internal strengths and weaknesses. SWOT analysis stands for (Strengths, Weaknesses, Opportunities, Threats). This study considers internal and external factors that can enhance or hinder a company's human resources function. Analysis of what a company can do to accelerate its transition from reactive to proactive mode to improve HR strategy and function. From the test results obtained strengths, namely the company has a Training Program for mechanics and engineers, Weaknesses, facilities are still incomplete, mechanics are not thorough in carrying out aircraft maintenance, Opportunities have good relationships with companies, companies that have mechanics and engineers who are still young have the opportunity to add new knowledge. Threats are that larger companies offer better facilities and guarantees, and companies find it difficult to find employees with the skills they need.